1981
DOI: 10.2172/6513057
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical studies of the film formation on lithium in propylene carbonate solutions under open circuit conditions

Abstract: The aim of this study is to investigate the kinetics of film formation on lithium in propylene carbonate solutions with different solutes and to determine some film characteristics such as resistance, conductivity, and thickness.Two principal ways of investigating these problems were chosen:electrochemical (galvanostatic pulse techniques) and optical (ellipsometry). This paper is dealing mainly with electrochemical measurements, while the results from ellipsometry will be presented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…for (L-d)<z<L [6] where z is the distance from the top to the bottom of the surface layer. When d << L, the thicknesses d and L are related to the ratio f2/fl by L/2d ~ f2/fl [7] according to the condition f2(L -d) = fi(L -d), where fi and f2 are the limiting values of each parameter for the second and first sublayers, respectively.…”
Section: Z= ~~ R~ ~=1 1 + J~o Ricimentioning
confidence: 99%
See 2 more Smart Citations
“…for (L-d)<z<L [6] where z is the distance from the top to the bottom of the surface layer. When d << L, the thicknesses d and L are related to the ratio f2/fl by L/2d ~ f2/fl [7] according to the condition f2(L -d) = fi(L -d), where fi and f2 are the limiting values of each parameter for the second and first sublayers, respectively.…”
Section: Z= ~~ R~ ~=1 1 + J~o Ricimentioning
confidence: 99%
“…Breiter and Dunn (4) showed that the reaction overpotential at the surface of the solid electrolyte was reduced and high sulfur utilization was realized by wrapping a high resistance mat at the surface of the solid electrolyte. Kawamoto (5,6) had clone a similar calculation, and proposed methods to realize high sulfur utilization and high energy efficiency in an actual sodium-sulfur cell. Kao and Wayner (7,8) modeled the transient behavior of the sulfur electrode by taking effects due to the variation of the chemical potential of sulfur.…”
Section: Lawrence Berkeley Laboratory Assisted In Meeting the Publica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies concentrated on the system of LiAlCl 4 in SOCl 2 solvent leading to a very thick SEI layer on the Li-metal electrode due to the highly reducing character of Li and the good oxidant SOCl 2 . [8][9][10] Also LiClO 4 , LiAsF 6 , and LiBF 4 in PC, and γ-butyrolactone [10][11][12][13] have been analyzed. For these systems two different models of ionic conduction z E-mail: michael@battronics.com based on Young's equation 14,15 and space-charge limited current 10,13 have been successfully applied.…”
mentioning
confidence: 99%
“…ROCO 2 Li). [44][45][46][47] Due to its complexity, Peled et al have proposed a complicated mosaic model of SEI, as seen in Fig. 4a.…”
Section: Secm Applicationsmentioning
confidence: 99%